PROVING BY **REMAINDER THEOREM:**

X^{4}-6X^{3}+16X^{2}-15X+10 = **(x ^{2}-2x-k)**(q(x)) +(x+a)

[any number=divisor x quotient + remainder] {q(x) is a function of x which i am considering as the quotient}

X^{4}-6X^{3}+16X^{2}-15X+10-x-a = **(x ^{2}-2x-k)**(q(x))

X^{4}-6X^{3}+16X^{2}-16X+10= **(x ^{2}-2x-k)**(q(x))+a

When x=2,

16-48+64-32+10=(4- 4-k)(q(x))+a

-22 = -k(q(x))+a

**a=k(q(x))-22**

When x= -k,

solve it and divide the equations the q(x) will be eliminated and solve the rest coz i am still figuring this out

GOOD LUCK